The Specification of Dielectric Ternary Compound BNT-BKT-BT - M. Jamal, Israa; K. Al-Shakarchi, Emad (Al-Nahrain Journal of Science, 2023)
The ternary ceramic compound (BNT-BKT-BT), like 0.855 (Bi0.5Na0.5TiO3) 0.115 (Bi0.5K0.5TiO3)-0.03 (BaTiO3) was prepared by solid-state reaction. Three different calcination processes as a function of temperature and time had been used as the candidate for the structural phase. The crystal structure analysis confirmed a rhombohedral and tetragonal phase regarding diffracted peaks within the morphotropic phase boundary (MPB). The dielectric behavior at different frequencies (1, 10, 100 kHz, and 3 MHz) and temperatures showed a maximum curie temperature at (295 °C) through a frequency (100 kHz). The XRD analyses showed the peak splitting observed around (2q = 40, and 46) related to the overlapping between many peaks mentioned by different phases. The appearance of the relaxer ferroelectric behavior emphasizes the agreement of the XRD analysis and dielectric measurement.